Influence of different growth regulators on the in vitro morphogenesis of an ornamental variety of carnation - Kiss, Zs. O.; Mándy, A. (International Journal of Horticultural Science, 2003)
Callus formation, as a prerequisite for the induction of somaclonal variability, was achieved successfully with certain molar ratios between 2,4-dichlorophenoxyacetic acid and benzyladenine. Regeneration of new plants from shoot apex meristems could be significantly improved by the combined addition of very low amounts of indolebutiric acid, benzyladenine and gibberelic acid, dissolved in the Murashige-Skoog nutrient medium. These in vitro treatments may contribute to a more efficient micropropagation of the Rimini variety of carnation.